Modelización de una micro red fotovoltaica aplicada a equipos de cocción por inducción para el reemplazo de GLP - Riofrio Trujillo, Augusto Jonathan (2015)
Due to the increasing use of electricity, cooking food has developed major changes, mainly with respect to fuel use from firewood, coal or fossil fuel derivatives up to the use of electricity. In the case of Ecuador, the government has decided to run a campaign about massive migration from LPG based cookers to induction cookers during the next three years, thanks to the policies of changing the Productive Matrix and also the diversification of the Energy Matrix. This works presents an alternative to feed these devices with electricity from a photovoltaic micro grid, which has the ability to store energy and use the grid energy to cover the peak demand at specific periods of time, following the established conditions in an operation model proposed for this kind of systems. Prior to the design and sizing of the photovoltaic micro grid, the electric induction cooker was characterized thorough an equivalent circuit and as a result a transfer function was obtained that allowed calculating the active power consumption of this equipment. The modeling of this system was performed using the Matlab Simulink tool, for a typical day of the months with highest and lowest solar resource, considering two extreme states of the battery bank at the start of the day. The results show that the use of distributed generation power applied to this equipment could mean for the user to stop using between 57% and 65% of the grid energy, even for the worst weather conditions considered. However, the economic analysis shows that, with the current costs, investment in this kind of facility is not short-term profitable.